Educational Psychology-Based Strategy for Instrumental Music Teaching in Normal College - Li, Yang (Frontiers in Psychology, 2021)
The study is intended to explore the teaching mode of instrumental music teaching in normal college, so as to have qualified instrumental music teaching talents. Based on relevant content of educational psychology, the current instrumental music teaching model of normal college should be reformed in terms of curriculum content, teaching mode, and teaching methods, and a more systematic and standardized education model should be established. As per Orff’s music teaching method, a music recommendation model is established based on the convolutional neural network model to provide students with a positive and happy learning environment for instrumental music, and music materials that meet their personal preferences and performance level through user data. The outcomes show that the designed music recommendation model has a music recommendation accuracy rate of 0.3 and a recall rate of 0.29 when the recommendation list is 30, which conforms to the general rules of the music recommendation system. The study is expected to provide reference for establishment of a standardized and systematic instrumental music teaching strategy in normal college.